Distribution, partitioning, and health risk assessment of organophosphate esters in a major tributary of middle Yangtze River using Monte Carlo simulation. (1st July 2022) - Lian, Maoshan; Lin, Chunye; Li, Yun; Hao, Xin; Wang, Aihua; He, Mengchang; Liu, Xitao; Ouyang, Wei
Highlights: Twelve organophosphate esters in river water, particulate and sediment were studied. TCPP dominated in the water and sediment while TBOEP dominated in particulate. OPE Partitioning between soluble and solid phases were quantified. STP effluents and mining industry were the main sources of OPEs in the ZR. The simulated health risks of OPEs in the water of the ZR were low. Abstract: Globally, organophosphate esters (OPEs) have attracted substantial attention because of their ubiquity in the environment, toxicity, and potential ecological and health risks. This study comprehensively investigated the occurrence, partitioning, and spatial distribution of nine ordinary monomeric OPEs (m-OPEs) and three emerging oligomeric OPEs (o-OPEs) in a major tributary of the middle Yangtze River, which is the Zijiang River (ZR), and their associated potential health risks. Total OPE concentrations ranged from 18.8 to 439 ng L −1, 1.40 to 19.1 ng L −1, and 3.71 to 77.3 ng g −1 dw in the surface water, suspended particulate matter (SPM), and sediment, respectively. Tris (2-chloroisopropyl) phosphate (TCPP) dominated the water (61.3%) and sediment (60.1%) samples, whereas tris (2-butoxyethyl) phosphate (TBOEP) was present in the SPM (59.0%) samples. The proportion of o-OPEs was low in all three media, ranging from 0.60% to 1.90%. Field-based log Koc values of the frequently detected OPEs were higher than those predicted by EPI Suite and were negatively correlated with temperature. The spatial distribution of OPEs in the water and hierarchical cluster analysis suggested that sewage treatment plant effluents and the mining industry were the main sources of OPEs in the ZR. The total noncarcinogenic and carcinogenic risks of OPEs in the water were low at the detected concentrations, even in the high-exposure scenario. Graphical abstract: Image, graphical abstract